Coherent ultrafast torsional motion and isomerization of a biomimetic dipolar photoswitch - Briand, Julien; Bräm, Olivier; Réhault, Julien; Léonard, Jérémie; Cannizzo, Andrea; Chergui, Majed; Zanirato, Vinizio; Olivucci, Massimo; Helbing, Jan; Haacke, Stefan (Physical chemistry chemical physics : PCCP, 2010)
Femtosecond fluorescence up-conversion, UV-Vis and IR transient absorption spectroscopy are used to study the photo-isomerization dynamics of a new type of zwitterionic photoswitch based on a N-alkylated indanylidene pyrroline Schiff base framework (ZW-NAIP). The system is biomimetic, as it mimics the photophysics of retinal, in coupling excited state charge translocation and isomerization. While the fluorescence lifetime is 140 fs, excited state absorption persists over 230 fs in the form of a vibrational wavepacket according to twisting of the isomerizing double bond. After a short "dark" time window in the UV-visible spectra, which we associate with the passage through a conical intersection (CI), the wavepacket appears on the ground state potential energy surface, as evidenced by the transient mid-IR data. This allows for a precise timing of the photoreaction all the way from the initial Franck-Condon region, through the CI and into both ground state isomers, until incoherent vibrational relaxation dominates the dynamics. The photo-reaction dynamics remarkably follow those observed for retinal in rhodopsin, with the additional benefit that in ZW-NAIP the conformational change reverses the zwitterion dipole moment direction. Last, the pronounced low-frequency coherences make these molecules ideal systems for investigating wavepacket dynamics in the vicinity of a CI and for coherent control experiments.